Getting out of a contract : a practical guide for business - Rose, Adam, 1966- (Gower, 2001)
"This book is written by three commercial lawyers. Their clients often ask them as much for help in getting out of a contract as in getting them into one in the first place. Built around two business case studies, this book highlights the various legal issues that a business must address when faced with a contract it wants to walk away from. In the first instance the business needs to discover whether it is as shackled by a contract as it thinks it is. In many cases a contract is not as binding as it might initially appear - Getting Out of a Contract explains the circumstances in which this applies. It then goes on to explore how to minimize the damage should the agreement be inescapable and helps the reader to understand what the consequences of any actions might be."--Jacket